Influence of Organizational Culture on Employee Engagement in Morocco - Habib, Fadoul (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the influence of organizational culture on employee engagement in Morocco. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that a strong, positive organizational culture can enhance employee engagement by fostering a sense of belonging, commitment, and motivation among employees. Elements such as shared values, open communication, and supportive leadership contribute to creating an environment where employees feel valued and are more likely to be engaged. When employees perceive that their organization cares about their well-being and professional growth, they tend to exhibit higher levels of dedication, enthusiasm, and discretionary effort in their roles. Conversely, a negative organizational culture, characterized by poor communication, lack of recognition, and unsupportive management, can lead to disengagement, decreased morale, and higher turnover rates. Therefore, cultivating a healthy organizational culture is crucial for boosting employee engagement, which in turn drives overall organizational performance and success. Implications to Theory, Practice and Policy: Social exchange theory, self-determination theory and cognitive dissonance theory may be used to anchor future studies on assessing the influence of organizational culture on employee engagement in Morocco. Implement culture assessment tools and surveys to regularly measure and assess employees' perceptions of organizational culture and its impact on their engagement levels. Integrate considerations of organizational culture and employee engagement into HR policies and practices, emphasizing the importance of cultural fit in recruitment, selection, and performance evaluation processes.